Crescimento e produtividade da cultura do feijão com diferentes disponibilidades de nitrogênio - Toso, Vinicius (2012)
The common bean has been considered a high nutrient demanding crop. To reach high grain yield, a balanced macro and micronutrient fertilization is essential. Nitrogen (N) is the second mineral to be extracted in greater quantities by the crop. The aim of this study was to determine the effect of mineral nitrogen supplied by fertilization on growth and yield and inferring criteria to better managing fertilization practices for this crop. Experiments were conducted in two growing periods, inside an umbrella type polyethylene greenhouse. The first was from 02 March to 03 June, 2011 (autumn) and the second from September 21 to December 23, 2011 (spring). Cultivars were BRS Valente and Pérola, planted in pots using sand as substrate. Nitrogen concentrations of 5.12 (T1); 7.6 (T2); 10.12 (T3); 12.62 (T4) and 15.12 (T5) mmol L-1 were supplied by fertigation using a complete nutrient solution. Significant differences were observed in grain yield, number of pods, weight of thousand kernels and shoot growth, being higher in spring. Grain yield and number and shoot growth of both cultivars decreased linearly by effect of increased N availability in the spring, but decreased only in the cultivar BRS Valente in autumn. Number of nodules per plant and root growth decreased in both cultivars. It was concluded that nodulation is inhibited by mineral N, increasing its availability does not enhance growth and grain yield and that nitrogen fertilization after planting this crop can be avoided.